(untitled) (Journal of Applied Oral Science, 2011)
Adequate denture hygiene can prevent and treat infection in edentulous patients. They are usually elderly and have difficulty for brushing their teeth. OBJECTIVE: This study evaluated the efficacy of complete denture biofilm removal using chemical (alkaline peroxide-effervescent tablets), mechanical (ultrasonic) and combined (association of the effervescent and ultrasonic) methods. MATERIAL AND METHODS: Eighty complete denture wearers participated in the experiment for 21 days. They were distributed into 4 groups (n=20): (1) Brushing with water (Control); (2) Effervescent tablets (Corega Tabs); (3) Ultrasonic device (Ultrasonic Cleaner, model 2840 D); (4) Association of effervescent tablets and ultrasonic device. All groups brushed their dentures with a specific brush (Bitufo) and water, 3 times a day, before applying their treatments. Denture biofilm was collected at baseline and after 21 days. To quantify the biofilm, the internal surfaces of the maxillary complete dentures were stained and photographed at 45º. The photographs were processed and the areas (total internal surface stained with biofilm) quantified (Image Tool 2.02). The percentage of the biofilm was calculated by the ratio between the biofilm area multiplied by 100 and the total area of the internal surface of the maxillary complete denture. RESULTS: The Kruskal-Wallis test was used for comparison among groups followed by the Dunn multiple-comparison test. All tests were performed respecting a significance level of 0.05. Significant difference was found among the treatments (KW=21.18; P